Coping with English language challenges in an M. Ed. TESL program : a case study / Ilham Alia Mat Isa - Mat Isa, Ilham Alia (2014)
Postgraduate studies have become a phenomenon nowadays. Despite the fact that the postgraduates are expected to be independent and autonomous adult learners, researches have proven that they face numerous challenges in learning. Hence, this study is conducted with the purpose of identifying one of the challenges faced by the postgraduates: English language challenges and the coping strategies employed in encountering the difficulties faced. All four vital language skills are studied, which are speaking, listening, reading and writing skills. This qualitative case study was conducted to four groups of respondents from different modes (part-time and fulltime) and semesters (1st and 3 rd semesters). In collecting the data, group interviews were conducted. Then, the recordings were transcribed and analysed. It was found that there are various language challenges faced by the respondents in speaking, listening, reading and writing. It was acknowledged that the language challenges encountered affect the postgraduates in their studies to some extent. Moreover, they have suggested varieties of coping strategies in dealing with all the language challenges mentioned. Interestingly, the coping strategies utilised have helped them in coping with the language challenges encountered. Undeniably, more researches need to be conducted in identifying the difficulties faced in utilising English in postgraduate studies and more possible solutions needed in dealing with the language difficulties. Hence it is highly recommended that the stakeholders, such as lecturers, the Institute of Postgraduate Studies, curriculum developer and the students take possible and practical action in identifying the challenges and solutions prevail in postgraduate studies.